An ultra-thin interlayer bimetallic sulfide for enhancing electrons transport of supercapacitor electrode. (15th November 2022) - Luo, Lili; Dai, Juguo; Xia, Long; Wang, Xiaohong; Xie, Hongmei; Tang, Zhenbin; Zuo, Haiyan; Xu, Yiting; Dai, Lizong
Abstract: Improving the sluggish reaction kinetics and intrinsic inferior electrical conductivity of metal oxides has always been a difficult and important issue. Integration engineering is proposed to effectively solve the above problem, namely, composite modification of metal oxides by materials with high conductivity and high specific surface area. Herein, a nanobelt of bimetallic sulfide/transition metal oxide (CoNiS/MoO3, CSM) composite is designed to improve the electrical conductivity of metal oxides without affecting the morphologic characteristics of materials. Thin-layer CoNiS acts as a channel for electrons and provides a protection for internal metal oxides. And then, in-situ polymerization polyaniline is utilized to strengthen the overall material and improve the specific surface area of the composite material. The CoNiS/MoO3 @Polyaniline (CSMP) composites exhibit a considerably high specific capacitance (1884 F g −1 at 1 A g −1 ) and noticeable cycling capability (92.9 % capacitance retention at 20 A g −1 after 3000 cycles) in three-electrode systems. When CSMP composites are assembled into asymmetric supercapacitor devices, the resultant devices deliver a superior energy density of 86 Wh kg −1 at a power density of 840 W kg −1, admirable cycling stability of 95.6 % and high coulombic efficiency of 99.4 % after 10, 000 repeated cycles. In particular, the charge storage mechanism is analyzed in detail based on CV tests, revealing that the surface-controlled capacitive process gradually dominates as scan rate increases. The excellent electrochemical performance well confirms the superiority of the synergistic effects of each component and the elaborate design of the conducting interlayer. Graphical abstract: Unlabelled Image Highlights: A robust core/shell structure electrodes for highly stable asymmetric supercapacitors PANI layer is protective shell as well as main electrochemically active component with good hydrophilicity. Asymmetric supercapacitors assembled with CoNiS/MoO3 @Polyaniline ternary composites show a superior energy density.